Pengaruh Budaya Organisasi Dan Kepuasan Terhadap Kinerja Pegawai Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Maros - Roswiyanti Roswiyanti; Hermin andi Magga; Zulkarnain S (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
'The Effect of Organizational Culture and Job Satisfaction on Employee Performance at the Maros Regency Investment and Integrated One-Stop Service. '' Thon employee 40 people from the Maros Regency Investment and Integrated One-Stop Service. Methods of collecting data using questionnaires, document studies, and observations. Testing the analysis prerequisites includes descriptive percentage, validity, reliability, classic assumptions test, and hypothesis testing using SPSS 21 For Windows Software. Based on the results of the study concluded that the influence of organizational culture on employee performance is t counted at 3.571 with sig 0,001. Effect of job satisfaction on employee performance t count of 6,484 with sig 0,000. The influence of organizational culture and job satisfaction together (simultaneous) on employee performance is F count of 64,936 with sign 0,000. Thus organizational culture and job satisfaction have a positive and significant effect on employee performance. And from the calculation of the coefficient of determination of organizational culture and job satisfaction on employee performance by 77.8%.